(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. Una causa naturale e universale di estinzione del vincolo matrimoniale: la morte di uno dei coniugi - 3. Il Codice civile del Regno d’Italia del 1806. - 4. Il Codice civile austriaco esteso ai territori italiani nord-orientali - 5. L’esperienza giuridica dei c.d. divorzi “fiumani” nell’immediato (primo) dopoguerra - 6. Il divorzio nei territori dell’Africa orientale italiana ai tempi del fascismo - 7. L’ingresso in Italia, prima del 1970, di divorzi pronunciati all’estero - 8. Conclusioni. The historical evolution of the divorce in Italy from the Ages of Codifications to 1970 ABSTRACT: The purpose of this paper is to examine the Italian regulations that already provided for divorce from the Ages of Codifications to 1970. In this perspective, the Author argues that the Italian legislator, although in a fragmentary and discontinuous manner, already provided for divorce since 1806. Furthermore, the Author focuses on cases in which foreign divorce judgments have gained the civil recognition (“delibazione”) before the Italian divorce legislation came into force.